A questão sobre a eternidade do mundo segundo o Comentário de Tomás de Aquino ao De Caelo. - Pinto, Maryane Stella (2018)
The purpose of this work was to analyze the question of the eternity of the world in Thomas Aquinas in view of his reading to De Caelo of Aristotle. The work of Thomas Aquinas is vast, in addition to the Sum of Theology, the Corpus Thomisticum has pamphlets, disputed questions and comments; among the latter are those for the Bible, the Neoplatonic, Boethius, and Aristotle. The comments to Aristotle is the object of this work. The activity of commenting on the Philosopher was most probably inaugurated, according to Torrel, in the years between 1267 and 1269, hence he continued in this office at a rapid pace, especially after the translations of Guillermo de Moerbeke, an eminent translator, had a unique knowledge of the Greek language, which allowed him to translate a vast amount of philosophical works, mainly of Aristotle and other scientific ones. However, about this activity, a question arises: why did Thomas undertake to comment on almost all the works of Aristotle, what use would this arduous task confer upon him? First, this work will present Thomas's philosophical trajectory, as regards his office as a commentator of Aristotle, and how these questions are essential for the reading of Aquinas's comments to the Philosopher. Subsequently, a clipping will be presented in Thomas 'Commentary to De Caelo, specifically in Lessons 22-24, where Aquinas exposes Aristotle' s course on the question of the eternity of the world. And finally, this work will present how the Commentary on De Caelo influences Thomas' debate on the question of the eternity of the world, having as a point of support question 46 of the Sum of Theology.